Hajj and Hajj Attire for Bugis Women: A Phenomenological Study in Bone District, South Sulawesi, Indonesia - Nurhalida HS; Isbah, M. Falikul (DINIKA : Academic Journal of Islamic Studies, 2023)
For the Bugis people in South Sulawesi, Indonesia, hajj (pilgrimage to Mecca) is a religious practice that illustrates a balance between practicing Islamic teachings and preserving local culture. This article explores the construction of meaning in hajj practices among Bugis women through various rituals and attributes, including wearing hajj attire. Data were collected through fieldwork in Bone District, South Sulawesi in which we conducted interviews with Bugis women of different ages, levels of education, and social classes who had made the pilgrimage. Through a phenomenological approach, we found that the practice of Bugis hajj rituals, such as mappatoppo, is common among all Bugis women across different groups. However, the hajj attire varies and can be categorized into traditional, modern, and moderate. The variations are influenced by the level of education, access to information and technology, social status, knowledge of the Islamic religion, occupation, kinship and association, and generational groups. We argued hajj attire carries different functions for different Bugis women, i.e., social control, traditional identity, representation of past political memory, social status and legitimacy, and markers of exclusivity. This study contributes to the global talk about the mix between religious and cultural expression by showing a complex continuity and changes of the expression amid the modernization the Bugis people experience.